Contributing to the Study of Enzymatic and Chemical Glycosyl Transfer Through the Observation and Mimicry of Glycosyl Cations - Blériot, Yves (Synthesis, 2020)
This account describes our efforts dedicated to: 1) the design of glycomimetics aimed at targeting therapeutically relevant carbohydrate processing enzymes, and 2) the observation, characterization, and exploitation of glycosyl cations as a tool for studying the glycosylation reaction. These findings have brought important data regarding this key ionic species as well as innovative strategies to access iminosugars of interest.1 Introduction2 The Glycosyl Cation, A Central Species in Glycosciences2.1 A Selection of the Strategies Developed so far to Gain Insights into Glycosyl Cations Structure2.2 When Superacids Meet Carbohydrates3 Chemical Probes to Gain Insights into the Pseudorotational Itinerary of Glycosides During Glycosidic Bond Hydrolysis3.1 Conformationally Locked Glycosides3.1.1 The Xylopyranose Case3.1.2 The Mannopyranose Case3.2 Conformationally Flexible Iminosugars3.2.1 Nojirimycin Ring Homologues3.2.2 Noeuromycin Ring Homologues3.2.3 Seven-Membered Iminosugar C-Glycosides4 N-Acetyl-d-glucosamine Mimics5 Ring Contraction: A Useful Tool to Increase Iminosugar’s Structural Diversity6 Regioselective Deprotection of Iminosugar C-Glycosides to Introduce Diversity at C2 Position7 Conclusion
Keywords: carbohydrates; glycosyl cation; iminosugars; glycosidases; conformation; superacids